2015
DOI: 10.1177/096739111502300504
|View full text |Cite
|
Sign up to set email alerts
|

Qualifying Dispersion and Distribution of Carbon Nanotubes in Polyamide Matrix during Melt-Mixing by Flow Simulation

Abstract: This work aims at numerically simulating the flow of nanocomposites in a twin-screw mixer so as to develop a prediction tool of nanofiller dispersion and distribution in a polymer matrix during processing. The rheological behaviour of polyamide 6 / carbon nanotubes blends (PA6/MWCNT) containing from 1 to 5 wt.% of MWCNT was investigated over a large range of shear rates (0.1 to 100 s−1) and temperatures (230 to 245 °C). The macroscopic dispersion of the nanotubes was assessed by dynamic rheometry. Viscosity la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…14 Tuo et al 15 investigated the dispersion states of carbon black (CB) and carbon nanotube (CNT)-reinforced composites. Also, the dispersion and distribution of CNTs in polymer matrix during manufacturing procedure of nanocomposites were investigated by Loux et al 16 Shi et al 17 presented a micromechanical model for studying the effect of CNTs agglomeration on the effective elastic modulus of CNTR composites. It is assumed that a large amount of CNTs are concentrated in some local regions of the matrix and the volume fraction of CNTs is much more than the average volume fraction of CNTs.…”
Section: Introductionmentioning
confidence: 99%
“…14 Tuo et al 15 investigated the dispersion states of carbon black (CB) and carbon nanotube (CNT)-reinforced composites. Also, the dispersion and distribution of CNTs in polymer matrix during manufacturing procedure of nanocomposites were investigated by Loux et al 16 Shi et al 17 presented a micromechanical model for studying the effect of CNTs agglomeration on the effective elastic modulus of CNTR composites. It is assumed that a large amount of CNTs are concentrated in some local regions of the matrix and the volume fraction of CNTs is much more than the average volume fraction of CNTs.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, torque rheometry is usually used in polymer processing for characterizing the processing properties of polymeric materials. 8 10 In 2009, Freire et al 11 studied the processability of poly(vinylidene fluoride)/poly(methyl methacrylate) blends using a torque rheometry and found that the increase in the poly(methyl methacrylate) content improved the processability of the blends, in spite of an increase in the activation energy of flow.…”
Section: Introductionmentioning
confidence: 99%